2018
DOI: 10.1101/gr.239186.118
|View full text |Cite
|
Sign up to set email alerts
|

Selfish mutations dysregulating RAS-MAPK signaling are pervasive in aged human testes

Abstract: Service Email Alerting click here. top right corner of the article or Receive free email alerts when new articles cite this article-sign up in the box at the http://genome.cshlp.org/subscriptions

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
73
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(80 citation statements)
references
References 68 publications
6
73
0
1
Order By: Relevance
“…Hras G12V has been detected in human sperm of healthy donors and is allelic to Hras G12S , the most common mutation in Costello syndrome, which increases with sperm donor age [9]. Given that gain-of-function mutations in the RAS pathway mediate positive selection of human SSCs [26, 27] and that overexpression of an Hras G12V cDNA is tumorigenic [23], we hypothesized that an increasing burden of Hras G12V would be detectable over time following induction in the adult testis. To test this hypothesis, our inducible mutation model enabled us to follow the fate of Hras G12V -positive A undiff over time.…”
Section: Resultsmentioning
confidence: 99%
“…Hras G12V has been detected in human sperm of healthy donors and is allelic to Hras G12S , the most common mutation in Costello syndrome, which increases with sperm donor age [9]. Given that gain-of-function mutations in the RAS pathway mediate positive selection of human SSCs [26, 27] and that overexpression of an Hras G12V cDNA is tumorigenic [23], we hypothesized that an increasing burden of Hras G12V would be detectable over time following induction in the adult testis. To test this hypothesis, our inducible mutation model enabled us to follow the fate of Hras G12V -positive A undiff over time.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, Goriely et al coined the term "selfish spermatogonial selection" to describe the increase in the number of mutant sperm over time (i.e. male aging) caused by the mutation-driven clonal expansion process (Maher et al, 2018). Of note, Maher et al (2018) identified a mutational clone in human testes for the FGFR2 Ser372Cys, one of the mutations known to cause BSS.…”
Section: Discussionmentioning
confidence: 99%
“…male aging) caused by the mutation-driven clonal expansion process (Maher et al, 2018). Of note, Maher et al (2018) identified a mutational clone in human testes for the FGFR2 Ser372Cys, one of the mutations known to cause BSS. In situations like advanced paternal age and CBAVD, which are both characterized by poor spermogram parameters, the before-mentioned clonal expansion process would lead to a relative increase in the number of mutated sperm, compared to situations consistent with normal spermatogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that most de novo point mutations or small indels have a paternal origin [37], whereas large deletions are predominantly of maternal origin, as is the case with NF1 [38]. Advanced paternal age can substantially increase this tendency for de novo point mutations, particularly for mutations occurring in genes implicated in the RAS pathway [39,40]. Indeed, such mutations stimulate selfish selection during spermatogenesis in a process close to oncogenesis, leading to an over-representation of spermatozoids carrying these alterations over time.…”
Section: Discussionmentioning
confidence: 99%